Evaluation of zincated nanoclay polymer composite in releasing Zn and P and effect on soil enzyme activities in a wheat rhizosphere. (5th August 2019) - Mandal, Nintu; Datta, Samar C.; Manjaiah, Kanchikeri M.; Dwivedi, Brahma S.; Kumar, Rajesh; Aggarwal, Pramila
Abstract: Zinc deficiency in soil is a widespread global phenomenon, resulting in smaller Zn content in cereal grains, particularly in wheat. Conventional fertilizers (ZnSO4 ·7H2 O or ZnSO4 · H2 O) resulted in low recovery efficiency (1–5%). An innovative fertilizer formulation was synthesized using nanoclay (having at least one dimension <100 nm), copolymer (acrylic acid and acrylamide as monomers), N, N‐Methylenebisacrylamide (NNMBA) as a crosslinking agent and ammonium persulphate (APS) as initiator. Zinc was added as Zn‐citrate during polymerization reactions. The product was named zincated nanoclay polymer composite (ZNCPC) containing 6.59% total Zn. The nanocomposite was evaluated in a laboratory incubation experiment and the data showed that it acted as a controlled release Zn formulation. Two doses of ZNCPC (5.0 mg Zn kg −1 and 2.5 mg Zn kg −1 ) were tested in pot experiments and compared with ZnSO4 ·7H2 O (5.0 mg Zn kg −1 ) in two Zn‐deficient soils (Soil I and Soil II) at the crown root initiation (CRI) and heading initiation (HI) stages in rhizosphere (with plants) and non‐rhizosphere (without plants) soil. The nanocomposite significantly increased DTPA‐extractable Zn (DTPA‐Zn), Olsen‐P and enzyme activities in rhizosphere soil. Citrate released during degradation of ZNCPC in soil solubilized native or applied P, which in turn increased Olsen‐P content in soil. Zinc content in wheat biomass at the HI stage increased to 88 and 87% in Soils I and II, respectively, compared to ZnSO4 ·7H2 O. There were positive and significant correlations among DTPA‐Zn, Olsen‐P and soil enzyme activities across growth stages and soil types. The ZNCPC proved to be an innovative and promising fertilizer formulation in a wheat rhizosphere that needed to be evaluated in a long‐term field experiment for its benefit:cost ratio and widespread adaptability. To explore an increase in Zn use efficiency the novel ZNCPC formulation was applied in a wheat rhizosphere. As there was an increase in DTPA‐Zn, Olsen‐P and soil enzyme activities, ZNCPC proved to be an innovative promising fertilizer formulation. Highlights: To explore an increase in Zn use efficiency. Novel ZNCPC formulation was applied in wheat rhizosphere. Increase in DTPA extractable Zn, Olsen‐P and soil enzyme activities. ZNCPC proved to be an innovative promising fertilizer formulation.